Efficacy of whitening toothpastes: Integrative review - Silva, Letícia Maya Gomes de Oliveira; Timóteo, Luanny Calheiros Dutra; Filho, Hibernon Lopes Lima; Vasconcelos, Rafaela Andrade de; Romão, Dayse Andrade; Silva, Marcos Aurélio Bomfim da; Santos, Natanael Barbosa dos; Brum, Cristine D’Almeida Borges; Lins, Rodrigo Barros Esteves; Rodrigues, Raphaela Farias (Seven Editora, 2024)
Recently, there has been a growing interest in oral aesthetics, driving the demand for brighter smiles. In response to this demand, the market has introduced a variety of off-the-shelf teeth whitening products, such as toothpastes, increasing the interest and demand of the public. The aim of this study was to conduct an integrative literature review on the efficacy of whitening toothpastes. For data collection, searches were made in databases such as: PubMed, Scielo and LILACS. The following descriptors were used as search criteria: whitening dentifrices AND effectiveness. A total of 25 articles published between 2018 and 2023 were selected, in Portuguese and English, to refine the research and enable higher quality. Regarding the effectiveness of whitening toothpastes, it was possible to observe that most studies indicate such products as significantly effective in extrinsic teeth whitening, but with lower efficacy than other whitening methods. DOI:https://doi.org/10.56238/sevened2024.007-068